2021
DOI: 10.3389/fpubh.2021.562437
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Anxiety During the Early Phase of the COVID-19 Pandemic in Sweden

Abstract: In this cross-sectional study we aimed to assess symptoms of depression and anxiety at an early stage of the COVID-19 pandemic, and to explore factors predictive of these mental health outcomes. A sample of 1,503 participants, recruited from the general Swedish population, completed an online survey distributed through social media. In this sample, 22.2% reported clinically significant levels of depressive symptoms (PHQ-9 ≥ 10) and 10.9% indicated possible major depression using the PHQ-9 algorithm. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
2
19
3
Order By: Relevance
“…Our study showed that younger age and unmarried status were persistent risk factors for anxiety over the year of this study. Similar to our findings, previous studies have shown that younger age was a significant predictor of anxiety during the COVID-19 pandemic [ 13 ]. The movement restrictions and social isolation associated with the pandemic could have resulted in more anxiety symptoms [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study showed that younger age and unmarried status were persistent risk factors for anxiety over the year of this study. Similar to our findings, previous studies have shown that younger age was a significant predictor of anxiety during the COVID-19 pandemic [ 13 ]. The movement restrictions and social isolation associated with the pandemic could have resulted in more anxiety symptoms [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Such limitations in social life could have contributed to their persistent anxiety over time. In addition, the literature reported a supportive social system as a protective factor against anxiety during the COVID-19 pandemic [ 13 , 46 ]. A French study showed that loneliness increased the risk of anxiety during COVID-19 lockdowns [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found mild to moderate correlations between economic difficulties and the studied mental health outcomes, in contrast to earlier results from Sweden by Rondung, Leiler, Meurling and Bjärtå (2021).…”
Section: Other Considerations and Future Perspectivescontrasting
confidence: 99%